Microleakage after Thermocycling of Three Self-Etch Adhesives under Resin-Modified Glass-Ionomer Cement Restorations - Sabine O. Geerts; Laurence Seidel; Adelin I. Albert; Audrey M. Gueders (International Journal of Dentistry)
This study was designed to evaluate microleakage that appeared on Resin-Modified Glass-Ionomer Cement (RMGIC) restorations. Sixty class V cavities (h×w×l=2mm×2mm×3mm) were cut on thirty extracted third molars, which were randomly allocated to three experimental groups. All the buccal cavities were pretreated with polyacrylic acid, whereas the lingual cavities were treated with three one-step Self-Etch adhesives, respectively, Xeno III (Dentsply Detrey GmbH, Konstanz, Germany), iBond exp (Heraeus Kulzer gmbH & Co. KG, Hanau, Germany), and Adper Prompt-L-Pop (3M ESPE AG, Dental products Seefeld, Germany). All cavities were completely filled with RMGIC, teeth were thermocycled for 800 cycles, and leakage was evaluated. Results were expressed as means ± standard deviations (SDs). Microleakage scores were analysed by means of generalized linear mixed models (GLMMs) assuming an ordinal logistic link function. All results were considered to be significant at the 5% critical level (𝑃<.05). The results showed that bonding RMGIC to dentin with a Self-Etch adhesive rather than using polyacrylic acid did not influence microleakage scores (𝑃=.091), except for one tested Self-Etch adhesive, namely, Xeno III (𝑃<.0001). Nevertheless, our results did not show any significant difference between the three tested Self-Etch adhesive systems. In conclusion, the pretreatment of dentin with Self-Etch adhesive system, before RMGIC filling, seems to be an alternative to the conventional Dentin Conditioner for the clinicians as suggested by our results (thermocycling) and others (microtensile tests).